Peran Agama dalam Kesehatan Mental Perspektif AlQuran Pada Kisah Maryam Binti Imran - Muhammad Shodiq Masrur; Azka Salsabila (Pendidikan Agama Islam STIT Palapa Nusantara, 2021)
The Qur'an is the word and love of Allah to His servants. Humans living without the Qur'an will experience anxiety and loss of purpose in life. Because the Qur'an is a guide in all aspects and is able to provide solutions to all problems of human life, both in terms of physical or mental. The evidence has been proven true in the Letter of Mary, as Maryam bint Imran when experiencing mental life problems, can be resolved only by referring to the word of God. The purpose of this writing is to describe the role of religion in solving life's problems and healing psychics faced by Maryam Bint Imran. This type of research is literature, data sources taken by books, journals, relevant Qur'anic verses, data collection by means of (library research) and data analysis methods use descriptive and interpretive analysis. The results of this research are to strengthen faith and monotheism by worshiping in accordance with the guidance that Allah and the Apostle teach will lead people to happiness and mental health and be able to optimize the potential in humans.